CORRELATION BETWEEN MELASMA AND QUALITY OF LIFE IN WOMEN IN SEBANI VILLAGE, TARIK DISTRICT, AND SIDOARJO DISTRICT - Utomo, Zelda Fidellia Natasha; Dian Putri, Maria Patricia; Suwandito, L (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Melasma has another name chloasma, derived from the Greek word